(untitled) (Bangladesh Journal of Psychiatry, 2020)
Mental health in child and adolescents is an essential component of overall health. Disturbed children are more likely to be disturbed adults. Therefore, early detection and treatment is important to decrease the long term disability. The objective of the study was to determine the morbidity pattern of psychiatric disorders among patients of pediatric outpatient department of tertiary level hospitals. This cross-sectional study was conducted from July 2012 to February 2013 in pediatric outpatient department of three prime tertiary level hospitals of Dhaka, Bangladesh. Purposive sampling technique was used and sample size was 240. A Semi- structured questionnaire containing socio-demographic and other relevant clinical information and the parent version of Development and Well Being Assessment (DAWBA) were applied. The results showed that most (70.8%) of the respondents were of 5 to 10 years’ age group with a male preponderance (54.2%). Out of 240 respondents, 44 (18.3%) were found with psychiatric morbidity. Categorically emotional disorder was 14.6%, behavioral disorder was 9.2% and developmental disorder was 0.4%. Hyperkinetic disorder (5.4%) and Oppositional defiant disorder (2.9%) were the most frequent diagnoses, followed by Obsessive compulsive disorder (2.5%). 29.5% of psychiatric cases were associated with other comorbid psychiatric diagnoses. Respondents with minor physical illness were mostly found with psychiatric morbidity (43.2%). Multiple patterns of psychiatric disorders were identified among the respondents. Therefore, the need to step up to the clinical and referral approaches is imperative to this special segment of children of our society. Bang J Psychiatry June 2017; 31(1): 1-6